Satisfacción al cliente de la Boutique “Jaez” de la ciudad de Babahoyo. - Monserrate Monar, Noemí Marisol (2022)
The case study entitled "Customer Satisfaction of the Boutique" JAEZ" of the City of Babahoyo, as an important point that is dedicated to the sale of women's clothing such as: blouses, dresses, pants, skirts, t-shirts, and jewelry In general, its general objective is to determine the factors that affect the process of Customer Satisfaction, through a survey of consumers of the "JAEZ" Boutique, the inductive-deductive method and techniques such as: surveys and interviews were applied. conclude the following: The case study is framed under the guidelines established by the Technical University of Babahoyo with which it has been tried to establish the problems raised in the "JAEZ" Boutique, the attention provided by employees when addressing customers to make their respective purchases of their products. For which it was suggested that employees should be trained to improve the treatment of buyers and that they receive good advice when purchasing a certain product and feel satisfied, so this generates a negative effect for the Boutique since it runs the risk of losing fixed customers due to the different factors that have been studied in this present case study. It is like a common logic, that a company without sales runs the risk of definitive closure. These and other negative peculiarities that affect the company are detailed in greater depth in the development of this study.